Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de ninos/as de los Centros Infantiles del Buen Vivir Caritas Felices y Estrellita Iluminando el Futuro MIES, Loja 2014 - 2015 - Espinosa Espinosa, Valeria del Cisne (2015)
The research entitled “KNOWLEDGE AND PRACTICES ABOUT PREVENTION AND MANAGEMENT OF ACUTE DIARRHEAL DISEASE, IN MOTHERS OF CHILD/CHILDREN OF GOOD LIVING CARITAS FELICES Y ESTRELLITA ILUMINANDO EL FUTURO CENTERS, MIES LOJA 2014-2015. Its main objective was to determine knowledge and maternal practices about prevention and age management in children under 5 years. It is a descriptive work, allowed measure and evaluate aspects of the phenomenon under investigation. The sample consisted of 72 participants who were given a survey to assess the level of knowledge about prevention and management of age. It was determined that most mothers know about the significance of age, but likewise in the opposite direction unknown factors that trigger the disease, which is reflected in daily practice and that most participants have wrong practices and attitudes towards management of this disease, at home, against a minority that chooses knowing and appropriate in the management of the same measures. Keywords: knowledge, practices, handle, prevention, diarrhea.